Development of Chemical Practicum Guide Oriented Chemoentrepreneurship in Colloid Synthesis - Imas Eva Wijayanti; Rina Rahayu; Solfarina Solfarina (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2020)
The large number of high school graduates who do not continue to college and their skills are not trained results they not being absorbed in the world of work. This problem can be solved by honing a skill, one of which is the ability to combine knowledge about chemistry with the manufacture of colloidal products. This study aims to produce a product in the form of chemical practicum guides for making chemoentrepreneurship-oriented colloids. This research used the R&D design with 3D Models (Define, Design, and Develop). The research begins with a needs analysis (Define), then design prototype through selecting the media, determining the format, and content of the product to be produced (Design), and the product validation stages through criticism or suggestions from the validators (Develop). The subjects of this study were students of class XI MAN 4 Pandeglang, who were selected by purposive sampling. Data validation results were analyzed using the Aiken'V method, and student response questionnaires to the product were measured using a Likert scale. The validation results of the product for each aspect of the practicum guides have a value of 0.78 (Aiken'V minimum table 0.76) and are declared valid. The product's limited trial results through a student response questionnaire obtained an average score of 93.8 with very good criteria. Data analysis results on the assessment of colloidal products in the form of student ability to make ice cream and simple water purifiers in groups 1, 2, 3, and 4 were 84.95; 79.57; 84,45; and 85.15. These results indicate that the research product in the form of a chemical colloid guideline can trigger students' creative and innovative skills.